2011
DOI: 10.1155/2011/524918
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Making of Nurses Working in Hospital Settings

Abstract: This study analyzed nurses' perceptions of clinical decision making (CDM) in their clinical practice and compared differences in decision making related to nurse demographic and contextual variables. A cross-sectional survey was carried out with 2095 nurses in four hospitals in Norway. A 24-item Nursing Decision Making Instrument based on cognitive continuum theory was used to explore how nurses perceived their CDM when meeting an elective patient for the first time. Data were analyzed with descriptive frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 31 publications
2
81
2
5
Order By: Relevance
“…This study findings support studies in the nursing literature that a residency program can have a positive impact on clinical decision-making (AL-Dossary et al, 2014: Bratt, 2013Bratt & Felzer, 2011Higuchi & Donald, 2002;Oermann & Garvin, 2002;Siew Eng et al, 2011;Torunn Bjørk & Hamilton, 2011). The findings of this study have implications for education, administration, and research; each recommendation is discussed and provided below based on the study's findings.…”
Section: Discussion Of Findingssupporting
confidence: 77%
See 1 more Smart Citation
“…This study findings support studies in the nursing literature that a residency program can have a positive impact on clinical decision-making (AL-Dossary et al, 2014: Bratt, 2013Bratt & Felzer, 2011Higuchi & Donald, 2002;Oermann & Garvin, 2002;Siew Eng et al, 2011;Torunn Bjørk & Hamilton, 2011). The findings of this study have implications for education, administration, and research; each recommendation is discussed and provided below based on the study's findings.…”
Section: Discussion Of Findingssupporting
confidence: 77%
“…Age, overall GPA, and enrollment in a residency program were the primary variables in this study since in the nursing literature it was found that they predict clinical decisionmaking skills (AL-Dossary et al, 2014: Bratt, 2013Bratt & Felzer, 2011Higuchi & Donald, 2002;Oermann & Garvin, 2002;Siew Eng et al, 2011;Torunn Bjørk & Hamilton, 2011). Although marital status has been found to shown…”
Section: Methodsmentioning
confidence: 91%
“…Although the instrument has not been intensely validated, it has been used on 2095 nurses in 4 Norway hospitals and a Crobanch's alpha of 0.863 was established [32] . The Crobanch's alpha in the current study was 0.760.…”
Section: Instrumentmentioning
confidence: 99%
“…* Central concept in nursing is care (Meleis, 2012) and clinical decision making forms the basis of patient care (Torunn and Hamilton, 2011). Nurses must be familiar with new methods to provide appropriate care for patients (Solomons and Spross, 2011), and use different sources of knowledge (Estabrooks et al, 2005) as well as the best evidence to make decision (Majid et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…With progresses in technology and science and changing condition of patients, it is required that nurses combine their technical skills, professional knowledge and evidence -based in their practice, and base their practice (Kahouei et al, 2012) on research and evidence (Neak Peima and Izadi, 2011). Nurses should make appropriate decision to provide better care for patients, and to do so, they need to use several of information and valid knowledge resources (Torunn and Hamilton, 2011). An important point is that, nurse should pay attention to level of resources and use first level and high quality evidence and researched-based knowledge that is found in valid databases (Kahouei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%